The effect of working memory load on prefrontal cortex activation: An optical topography study - Hani, A.M. (Asian Research Publishing Network, 2015)
Working memory (WM) is a theoretical concept that represents the system responsible for cognitive brain functions such as language, planning and problem solving. Studies have suggested that negative mood states impair the WM system, which can be reflected through changes in WM task performance and in activation of specific parts of the brain such as the prefrontal cortex (PFC). In this study, the relationship between working memory load and the PFC activation is investigated without biasing of mood using an optical topography (OT) system. Three levels of N-back tasks were carried out on 14 healthy male university students. It is found that the OT modality as a less-constrained neuroimaging tool can effectively measure the haemodynamic changes at PFC, confirming a significant increase of PFC activation is associated with increase of WM load from 0-back to 1-back task. Â© 2006-2015 Asian Research Publishing Network (ARPN).